2022
DOI: 10.1101/2022.10.07.509566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UGDH promotes tumor-initiating cells and a fibroinflammatory tumor microenvironment in ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) is a global health burden, with the poorest five-year survival rate of the gynecological malignancies due to diagnosis at advanced stage and high recurrence rate. Recurrence in EOC is driven by the survival of chemoresistant, stem-like tumor-initiating cells (TICs) that are supported by a complex extracellular matrix (ECM) and immunosuppressive microenvironment. To target TICs to prevent recurrence, we identified genes critical for TIC viability from a whole genome siRNA screen.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have shown that UGDH is positively associated with the development of epirubicin resistance and regulation of the ECM in breast cancer [15]. Upregulation of UGDH has been associated with metastasis in ovarian cancer, where it regulates tumor-initiating cells affecting the tumor microenvironment [12]. And it may be related to melanoma development and progression [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that UGDH is positively associated with the development of epirubicin resistance and regulation of the ECM in breast cancer [15]. Upregulation of UGDH has been associated with metastasis in ovarian cancer, where it regulates tumor-initiating cells affecting the tumor microenvironment [12]. And it may be related to melanoma development and progression [22].…”
Section: Discussionmentioning
confidence: 99%
“…The role of UGDH in cancer has received extensive attention from researchers in recent years. Abnormally elevated UGDH expression has been reported to be associated with the development of malignant tumors such as lung cancer [8], hepatocellular carcinoma (HCC) [9], pancreatic ductal adenocarcinoma [10], breast cancer [11], ovarian cancer [12], prostate cancer [13], and glioblastoma [14], as well as being correlated with poor prognosis of a variety of cancers. UGDH has broad and diverse regulatory effects in cancer and is closely associated with tumor drug resistance [15], epithelial-mesenchymal transition [16], and cellular localization [17], participating in pathways such as the sugar nucleotide biosynthetic [5] and TGFβ signaling [18] pathways, which is of great signi cance for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%